2018
DOI: 10.1136/bmjopen-2017-020080
|View full text |Cite
|
Sign up to set email alerts
|

Quality of health literacy instruments used in children and adolescents: a systematic review

Abstract: ObjectiveImproving health literacy at an early age is crucial to personal health and development. Although health literacy in children and adolescents has gained momentum in the past decade, it remains an under-researched area, particularly health literacy measurement. This study aimed to examine the quality of health literacy instruments used in children and adolescents and to identify the best instrument for field use.DesignSystematic review.SettingA wide range of settings including schools, clinics and comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
130
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(142 citation statements)
references
References 78 publications
2
130
1
9
Order By: Relevance
“…In this study, Pearson correlation coefficients between Gen-HL and three sub-dimensions scores showed these coefficients with Gen-HL were found as 0.780, 0.836 and 0.807 with the sub-dimensions HC, DP and HP, respectively and higher correlation coefficient between these sub-dimensions (Table 2). These values were closer to several studies results in European and Asian countries and a study in Brazil showed similar results [15,19,[25][26][27][28][29]. Regarding item-scale convergent validity, most of these items evidently had shown to have very weak correlation (rho) ranging from − 0.022 to 0.450 with variations within these range for general health literacy and for each of these three subscales in both categories of participants ( Table 3).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, Pearson correlation coefficients between Gen-HL and three sub-dimensions scores showed these coefficients with Gen-HL were found as 0.780, 0.836 and 0.807 with the sub-dimensions HC, DP and HP, respectively and higher correlation coefficient between these sub-dimensions (Table 2). These values were closer to several studies results in European and Asian countries and a study in Brazil showed similar results [15,19,[25][26][27][28][29]. Regarding item-scale convergent validity, most of these items evidently had shown to have very weak correlation (rho) ranging from − 0.022 to 0.450 with variations within these range for general health literacy and for each of these three subscales in both categories of participants ( Table 3).…”
Section: Discussionsupporting
confidence: 88%
“…Health literacy is a multidimensional and multifaceted construct concept [13] so that there exists variation in indicators and measurement tools [14], [15]. Taking these in account, the European Health Literacy (HLS-EU) project that took place 2009-2012 supported and funded by the European Commission and the national partners in the HSL-EU Consortium aiming to measure health literacy in Europe, establish networks and to promote health literacy in Europe [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, the field of adolescent health literacy has gained momentum globally [1][2][3][4]. As a personal asset, it highlights the empowerment of adolescents and their own rights of citizenship in society [5].…”
Section: Introductionmentioning
confidence: 99%
“…Given that health literacy is a broad concept with a wide range of assessment tools [3], it is essential to consider it within a specific context for a specific content [22]. In this present study, we defined adolescent health literacy as "an individual's ability to find, understand and use health information and services to promote and maintain good health" [23] and applied it into school settings.…”
Section: Introductionmentioning
confidence: 99%
“…However, although HL in young people has gained increasing attention in the past decade, studies analyzing HL in adolescents and young adults are still limited (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%